The population of the Kaliningrad region and the digital economy: a sociological analysis - Boris B. Podgorny (Immanuel Kant Baltic Federal University, 2021)
Since 2019, the Kaliningrad region has been running a regional digital transformation programme as part of the national initiative The Digital Economy of the Russian Federation. The programme seeks to improve the quality of life by creating information infrastructure and streamlining public administration. The regional Ministry of Digital Development has already presented an interim report on its implementation focused, however, mainly on the economic performance.